[Jelena Džankić. 2019. The Global Market for Investor Citizenship: Politics of Citizenship and Migration, Cham: Palgrave Macmillan (Politics of Citizenship and Migration). xiii + 225 pp., ISBN: 978-3-030-17631-0 (Hardcover), 978-3-030-17632- 7 (eBook), € 64.99/€ 53.49] - Přívara, Andrej, 1983-
Recenzia knihy Jeleny Džankić - The Global Market for Investor Citizenship: Politics of Citizenship and Migration.